THE PRACTICES, EFFECTIVENESS AND CHALLENGES OF COMMUNAL RESOURCE CONFLICT MANAGEMENT ALONG NORTH WOLLO AMHARA AND NEIGHBORING AFAR IN ETHIOPIA - Fikeryohannes Gebresilasie Abebe; Adamtey Ronald; Owusu-Ansah J.K. (African Journal on Land Policy and Geospatial Sciences)
The area along North Wollo Amhara and neighbouring Afare regional states have been exposed to small scale prolonged violent communal resource conflicts. Many factors drive and triggers for these violent conflicts which includes institutional, political, economic, and environmental change. Therefore, the objective of the research is to explore the practices, effectiveness and challenges of the communal resource conflict resolution and management institutions through case study research design.  To answer these objectives, we used survey, interview, and Focus group discussion. Both qualitative and quantitative data were collected from 354 household heads, 3 focus group discussions, 43 key informants, and analyzed the data through descriptive statistics and thematic analysis. The research result confirmed that both the customary and statutory institutions show low achievements in inter-community negotiation, facilitation, inter-community conflict analysis, and inter-community communication, strikethrough they are good in mediation. The luck of conflict resolution skills has been playing to continue the conflicts as protracted one. Further, the unresolved resource use and ownership claim of water and grazing land between the two communities; government development program without local community consultation in the contested land; illegal arms circulation; violence culture; and the existing ethnic politics in the country have created a great challenge to strikethrough to solve the violent resource conflicts at the early stage. To calm the situations, the research recommended well defined resource and regional boundaries of the two people, creating strong conflict resolution institutions, and applying conflict transformation frameworks.